2001
DOI: 10.1007/s005420100092
|View full text |Cite
|
Sign up to set email alerts
|

A flexible encapsulated MEMS pressure sensor system for biomechanical applications

Abstract: The use of pressure sensors made of conductive polymers is common in biomechanical applications. Unfortunately, hysteresis, nonlinearity, non-repeatability and creep have a signi®cant effect on the pressure readings when such conductive polymers are used. The objective of this paper is to explore the potential of a new¯exible encapsulated micro electromechanical system (MEMS) pressure sensor system as an alternative for human interface pressure measurement. A prototype has been designed, fabricated, and charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 1 publication
0
44
0
Order By: Relevance
“…For example silicon has been used for the fabrication of accelerometers [6,7], pressure sensors [8][9][10], resonators [11][12][13], or chemical/bio-chemical sensors [14][15][16]. For emerging MEMS applications such as bio-sensing, diamond appears to be a promising alternative material to silicon.…”
Section: Introductionmentioning
confidence: 99%
“…For example silicon has been used for the fabrication of accelerometers [6,7], pressure sensors [8][9][10], resonators [11][12][13], or chemical/bio-chemical sensors [14][15][16]. For emerging MEMS applications such as bio-sensing, diamond appears to be a promising alternative material to silicon.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore critical to ensure the availability of an accurate and efficient technique of measuring this type of pressure. Among the key requirements of the pressure sensor specification for the application is its pressure range, output linearity and low hysteresis [5]. It is suggested that for walking analysis, pressure sensor should be able to measure up to 1000kPa, or 10kgcm -2 (about 100Ncm -2 ) [6].…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of commercially available foot-pressure sensors at current but due to specification limitations, these sensors are not fully fulfilling the requirement of various biomechanical applications. The limitations include the specified pressure span, physical sensor dimensions [7] and hysteresis [5]. These weaknesses may cause erroneous readings or even worse, the malfunctioning of the device as some application may introduce pressure values way too far beyond the specified range.…”
Section: Introductionmentioning
confidence: 99%
“…Even though a rigid force transducer usually allows great accuracy of force measurement and multiaxial application, the user's natural motion can be disturbed due to rigidity and weight of the sensor. The foot plantar pressure sensor should be thin and flexible and light-weight, less than 300 g, for natural gait of the user [48,49]. The proposed GRF sensor was made of silicone tubes covered with fabrics to be light and soft.…”
Section: Introductionmentioning
confidence: 99%